Comprehensive Nitrogen Budgets for Controlled Tile Drainage Fields in Eastern Ontario, Canada. Issue 2 (1st March 2014) - Sunohara, M. D.; Craiovan, E.; Topp, E.; Gottschall, N.; Drury, C. F.; Lapen, D. R.
Abstract : Excessive N loading from subsurface tile drainage has been linked to water quality degradation. Controlled tile drainage (CTD) has the potential to reduce N losses via tile drainage and boost crop yields. While CTD can reduce N loss from tile drainage, it may increase losses through other pathways. A multiple‐year field‐scale accounting of major N inputs and outputs during the cropping season was conducted on freely drained and controlled tile drained agricultural fields under corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] production systems in eastern Ontario, Canada. Greater predicted gaseous N emissions for corn and soybean and greater observed lateral seepage N losses were observed for corn and soybean fields under CTD relative to free‐draining fields. However, observed N losses from tile were significantly lower for CTD fields, in relation to freely drained fields. Changes in residual soil N were essentially equivalent between drainage treatments, while mass balance residual terms were systematically negative (slightly more so for CTD). Increases in plant N uptake associated with CTD were observed, probably resulting in higher grain yields for corn and soybean. This study illustrates the benefits of CTD in decreasing subsurface tile drainage N losses and boosting crop yields, while demonstrating the potential for CTD to increase N losses via other pathways related to gaseous emissions and groundwater seepage.